1987
DOI: 10.1029/rg025i007p01441
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐chemical interactions and effects of changing atmospheric trace gases

Abstract: The problem concerning the greenhouse effects of human activities has broadened in scope frbm the CO2-climate problem to the trace gas-climate problem. The climate effects of non-CO 2 trace gases are strongly governed by interactions between chemistry, radiation, and dynamics. We discuss in delfiil the natuie of the trace gas radiative heating and describe the importance of radiative-chemical interactions within the troposphere and the stratosphere. We make an assessment of the trace gas effects on troposphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
127
3
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(138 citation statements)
references
References 143 publications
7
127
3
1
Order By: Relevance
“…The resulting change in surface temperature shown in Table 4 assumes that no climatic feedback processes occur in the atmosphere. These results are based on the studies of Rind and Lacis (1993), although similar results have been found with other models (Ramanathan et al, 1987). Fig.…”
Section: Projecting Future Changes In Forcingsupporting
confidence: 87%
See 1 more Smart Citation
“…The resulting change in surface temperature shown in Table 4 assumes that no climatic feedback processes occur in the atmosphere. These results are based on the studies of Rind and Lacis (1993), although similar results have been found with other models (Ramanathan et al, 1987). Fig.…”
Section: Projecting Future Changes In Forcingsupporting
confidence: 87%
“…This de®nition is based on earlier climate modeling studies, which indicated an approximately linear relationship between the global mean radiative forcing at the tropopause and the resulting global mean surface temperature change (e.g. Hansen et al, 1981;Ramanathan et al, 1985Ramanathan et al, , 1987. However, recent studies of greenhouse gases (e.g.…”
Section: Radiative Forcingmentioning
confidence: 99%
“…For a doubling of methane concentration from 1.6 to 3.2 ppmv, effects on surface temperature range from 0.2 K to 0.3 K (Wang et al, 1976;Donner and Ramanathan, 1980;Lacis et al, 1981;Owens et al, 1985;Ramanathan et al, 1987;MacKay and Khalil, 1991), with the differences in model results primarily relating to uncertainties in the band strengths for methane infrared absorption. For a doubling from 1.7 to 3.4 ppmv, Owens et al (1985) calculate a direct 0.34 K increase in surface temperature, along with an additional 0.26 K due to indirect effects from methane-induced effects on carbon dioxide and ozone.…”
Section: Direct Effectsmentioning
confidence: 99%
“…Other modeling studies have included increasing methane concentrations in studies evaluating scenarios for potential future changes in radiative forcing and global temperatures (Wang and Molnar, 1985;Ramanathan et al, 1985Ramanathan et al, , 1987WMO, 1985;Dickinson and Cicerone, 1986;Wang et al, 1986;Wigley, 1987;Hansen et al, 1988Hansen et al, , 1989IPCC, 1990. ) Table 2 the change in radiative forcing (Wm -2 ) due to increasing methane compared to total change due to all greenhouse gases as derived by IPCC (1996) for their high (IS92e), medium (IS92a), and low (IS92c) scenarios.…”
Section: Direct Effectsmentioning
confidence: 99%
See 1 more Smart Citation